Answer:
x = 13/3
Explanation:
Solve for x:
3×2 (x - 4) - 2 = 0
Hint: | Multiply 3 and 2 together.
3×2 = 6:
6 (x - 4) - 2 = 0
Hint: | Distribute 6 over x - 4.
6 (x - 4) = 6 x - 24:
6 x - 24 - 2 = 0
Hint: | Group like terms in 6 x - 24 - 2.
Grouping like terms, 6 x - 24 - 2 = 6 x + (-24 - 2):
6 x + (-24 - 2) = 0
Hint: | Evaluate -24 - 2.
-24 - 2 = -26:
6 x + -26 = 0
Hint: | Isolate terms with x to the left hand side.
Add 26 to both sides:
6 x + (26 - 26) = 26
Hint: | Look for the difference of two identical terms.
26 - 26 = 0:
6 x = 26
Hint: | Divide both sides by a constant to simplify the equation.
Divide both sides of 6 x = 26 by 6:
(6 x)/6 = 26/6
Hint: | Any nonzero number divided by itself is one.
6/6 = 1:
x = 26/6
Hint: | Reduce 26/6 to lowest terms. Start by finding the GCD of 26 and 6.
The gcd of 26 and 6 is 2, so 26/6 = (2×13)/(2×3) = 2/2×13/3 = 13/3:
Answer:x = 13/3